Computer studies through applications - Kennewell, Steve 1949- (Oxford University Press, 1989)
A fully applications-based GCSE course, providing comprehensive syllabus coverage in line with GCSE aims and objectives. It also provides a valuable resource for vocational and pre-vocational courses including BTEC and CPVE. Through the context of real applications, this book shows what people use computers for, how they use computers, how computers work and the effects of introducing computers and other new technology. Cases studies cover typical uses of micro-, mini- and mainframe computers; personal computer, control and data-processing applications; word-processing, database, spreadsheets and graphics packages; languages from first to fourth generation. The accompanying "Teacher's Resource Pack" contains answers to and notes on questions in the "Student's Book"; teaching guidance and suggestions for practical work; lists of objectives and terms for each chapter; over 60 pages of photocopiable worksheets containing mixed-ability material, extension problems, new applications and reinforcement material.